Clinical spectrum and genotype-phenotype associations of KCNA2-related encephalopathies - Masnada, Silvia; Syrbe, Steffen (Brain, 2017)
Mutations in KCNA2 have been reported as a cause of encephalopathy. Masnada et al. describe different phenotypes of KCNA2 encephalopathies associated with loss-